MicroRNA-21 in urologic cancers: from molecular mechanisms to clinical implications - Gan, Lifeng; Zheng, Liying; Zou, Junrong; Luo, Peiyue; Chen, Tao; Zou, Jun; Li, Wei; Chen, Qi; Cheng, Le; Zhang, Fangtao; Qian, Biao (Frontiers in Cell and Developmental Biology, 2024)
The three most common kinds of urologic malignancies are prostate, bladder, and kidney cancer, which typically cause substantial morbidity and mortality. Early detection and effective treatment are essential due to their high fatality rates. As a result, there is an urgent need for innovative research to improve the clinical management of patients with urologic cancers. A type of small noncoding RNAs of 22 nucleotides, microRNAs (miRNAs) are well-known for their important roles in a variety of developmental processes. Among these, microRNA-21 (miR-21) stands out as a commonly studied miRNA with implications in tumorigenesis and cancer development, particularly in urological tumors. Recent research has shed light on the dysregulation of miR-21 in urological tumors, offering insights into its potential as a prognostic, diagnostic, and therapeutic tool. This review delves into the pathogenesis of miR-21 in prostate, bladder, and renal cancers, its utility as a cancer biomarker, and the therapeutic possibilities of targeting miR-21.